Severe haemorrhagic diathesis due to acquired hypofibrinogenemia in a patient with early T-cell precursor acute lymphoblastic leukaemia/lymphoma: a case report - Spiezia, Luca; Riva, Marcello; Gurrieri, Carmela; Campello, Elena; Simioni, Paolo (Frontiers in Cardiovascular Medicine, 2024)
The most frequent haematological malignancy associated with acquired hypo/dysfibrinogenemia is multiple myeloma. We present an unusual case of severe haemorrhagic diathesis due to acquired hypofibrinogenemia in a patient with early T-cell precursor acute lymphoblastic leukaemia/lymphoma (ETP-ALL/LBL). A 57-year-old male was admitted to the General Internal Medicine Department of Padova University Hospital for acute massive haematomas of the left lower extremity associated with macrohaematuria. Coagulation tests showed prolonged prothrombin time, activated partial thromboplastin time and thrombin time due to isolated severe hypofibrinogenemia (antigen 0.70 g/L and activity 26%). The radiological workup showed a bulky lesion located in the anterior mediastinum, and a biopsy led to the diagnosis of ETP-ALL/LBL. Fibrinogen replacement therapy failed to correct the bleeding diathesis and we were able to exclude other frequent causes of acquired hypofibrinogenemia (i.e., liver dysfunction, fibrinogen-specific antibody or drug toxicity); therefore, we hypothesised that hypofibrinogenemia might stem either from enhanced removal of fibrinogen from the circulation or consumptive coagulopathy. Notably, only after initiating a specific chemotherapy treatment did the patient start showing improvement in bleeding symptoms and achieve normal fibrinogen levels.